Studi Tentang Faktor Penyebab Rendahnya Kemampuan Membaca - Ichyatul Afrom (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
Besides skilled concocted learners also gain insight, language, skill and information obtained from books. A positive influence intensity learners visit library consisting of several factors. Among the factors affecting desire to add insight, capability of language, and ably magicians, personal and by the pleasure appears as intrinsic motivators self when visiting the library. Aside from learners often visit the library. A collection of books at home has some role in the tracery of insight and skill in making a child authorship. The existence of the book readings at home then it would add to the learner the opportunity to always read in the library that is provided in the school. These factors are obtained based on the question form is deployed to collect data support in strengthening hiopesis received in this research. The results of this research show that there were significant effects between the intensity of a visit to the library to write skills learners. The more often the students visiting the library is getting better and is skilled in writing. With a proven testing the hypothesis that Y = 44,47 0, 38X. In addition to the value of (b) the positive values of b are also larger dar r table in the sample as many as 100 people i.e. 0,195. B calculate the value of 0.38 & gt; r tables there, meaning 0,195 positive influence the intensity of a visit to the library to write skills learners.